Deciphering the in vitro homo and hetero oligomerization characteristics of CXCL1/CXCL2 chemokines. Issue 34 (17th March 2016) - Gulati, Khushboo; Poluri, Krishna Mohan
Abstract : Murine GRO chemokines CXCL1(mKC)/CXCL2(MIP2) forms heterodimers and thus adding another layer of regulatory mechanism for leukocyte trafficking during infection/inflammation. Abstract : Chemokines share the fundamental property of oligomerization and regulate leukocyte migration via interacting with glycosaminoglycans and G-protein coupled receptors. Our studies on murine neutrophil activating chemokines CXCL1(mKC)/CXCL2(MIP2) deciphered their differential homo oligomerization potentials and heterodimer forming capabilities, thus adding another layer of regulatory mechanism for leukocyte trafficking during infection/inflammation.